Esophageal Papillomatosis Complicated by Squamous Cell Carcinoma. (2009) - Attila, Tan; Fu, Anna; Gopinath, Nanda; Streutker, Catherine J; Marcon, Norman E
Abstract : Esophageal papillomatosis is a very rare condition that is believed to have a benign clinical course. Recent reports underscore the potential development of a malignancy in association with squamous papillomatosis of the esophagus. A case of esophageal papillomatosis complicated by the development of esophageal invasive squamous cell carcinoma diagnosed after esophagectomy, despite multiple nondiagnostic endoscopic biopsies, is described. The patient also developed squamous cell carcinoma in the oral cavity and pyloric channel. The finding of extensive esophageal papillomatosis and unremitting dysphagia symptoms should prompt investigations into an underlying associated malignancy.